Quality of life in patients undergoing hemodialysis: Integrative review (Research, Society and Development, 2022)
Chronic Kidney Disease is one of the main causes of the need for renal replacement therapy. Patients undergoing this type of treatment present, in general, sedentarism and functional weakness, affecting the perception of quality of life. Given this context, the objective of this article is to verify the perception of quality of life of patients with chronic kidney disease undergoing hemodialysis. This is an integrative review, and the following databases were used for the research: Pubmed, Scielo, Lilacs, Medline, BDENF-Nursing and BVS. The screening process had the following inclusion criteria: answering the guiding question, in English, Portuguese or Spanish, and between 2017 and 2022. After the searches, a total of 10 articles were used. The epidemiological profile of patients undergoing hemodialysis found was of higher incidence in male patients, with low education and age range between 40 and 65 years. The quality of life of these patients on hemodialysis, determines a reduction in the performance of the professional role, physical and emotional function, indicating the existence of initial feelings of frustration, indignation and denial. This study perceived a reduction in the quality of life of hemodialysis patients, interfering mainly in the performance of professional role, patient satisfaction and sexual functions. Therefore, this study reaffirms the need to continue with new studies, in order to generate quality of life, ensure comprehensive health care and perform the prevention and reduction of diseases associated with the prolonged time of hemodialysis treatment.